For The Many, Not the Few: Case Analysis of Bukit Duri Forced Eviction in Jakarta - Arie Afriansyah (Rechtsidee, 2018)
The International Covenant on Civil and Political Rights and the International Covenant on Economic, Social and Cultural Rights allow states to conduct forced eviction as long as it is carried out within the given boundaries. This journal will comprehensively elaborate each standards given by the two international human rights covenants as well as the implementation of those standards in the cases of Human Rights Committee and Committee on Economic, Social and Cultural Rights. The standards will then be applied to analyze the case of forced eviction in Bukit Duri, South Jakarta, in the year of 2016. Based on the literature review and the interviews that have been conducted, it can be concluded that states can justify their action of forced eviction if it fulfills the standards of ‘lawful’ and ‘non-arbitrary’. The Bukit Duri forced eviction did not fulfill those standards.